Problems of Internationalizationof Higher Education Systems in Post-Soviet Countries (on the Exampleof Armenia and Belarus) - Zaslavskaya , Maria; Titarenko, Larisa (Journal of Sociology: Bulletin of Yerevan University, 2019)
Based on comprehensive sociological research on the problems of modernization of higher education systems, carried out as part of an international scientific project on the study of higher education in Armenia and Belarus, the article discusses the processes of internationalization of higher education systems in these countries. Some consequences and problems of the internationalization of higher education systems in Armenia and Belarus are examined in the context of the academic mobility of students and teaching staff, the processes of unification of educational programs, inter-university agreements and the expansion of education, and their features in the context of national higher education systems. The article emphasizes the need for a flexible approach in introducing the main components of the internationalization process, and their adaptation to national higher education systems.